Evaluation of phosphate rock sources and rate of application on oil palm yield grown on peat soils of Sarawak, Malaysia - Abdul Rahman, Zaharah; Gikonyo, E. W.; Silek, B.; Goh, K. J.; Soltangheisi, Amin (Asian Network for Scientific Information, 2014)
Malaysia has 2.4 million ha of peat and this type of soil is very poor in phosphorus and needs P application. As there are various sources of P fertilizer in the Malaysian market, it is crucial for growers to apply the most effective source for their crops. In this research, two sources of phosphate rocks available in the local fertilizer market from Christmas Island (CIPR) and Morocco (MPR) at four rates were evaluated for maximum yields of Fresh Fruit Bunches (FFB) from oil palm grown on peat soils in Sarawak, Malaysia. The CIPR and MPR at the rates of 0, 500, 1000 and 2000 g plam-1 year-1 were applied annually. FFB ha-1, average weight bunch-1 and leaf and soil nutrient concentrations were determined. Results showed that MPR treatments produced higher available soil P than CIPR treatments by average of 87% and also higher leaf P concentrations (up to 0.185%). Pearson’s correlation indicated that available soil P was negatively correlated with K, Mg, B, Cu and Zn but positively correlated with Ca. In addition, P concentrations in leaves were positively correlated with Ca, Mg, B and Zn but were negatively correlated with K and Cu. Correlation of yield parameters and leaf nutrient concentrations revealed that bunch weights were negatively correlated with leaf P concentrations, Mg and B, whilst the total yield was negatively correlated with Mg and B. Maximum yields were obtained at CIPR-2000 and CIPR-1000 treatments. By interpolation maximum yields in MPR would be attained at MPR-750 treatment.